Phytoniosomal gel of acalypha indica: a novel topical delivery system for anti-inflammatory activity (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
This study aimed to develop and evaluate an anti-inflammatory gel formulation utilizing Acalypha indica phytoniosomes. Acalypha indica, a traditional medicinal plant, possesses potent anti-inflammatory properties attributed to various bioactive compounds. Phytoniosomes are novel drug delivery systems that combine the therapeutic benefits of plant extracts (phytoconstituents) with the advantages of niosomes. They form stable complexes that enhance the bioavailability, stability, and targeting of the phytoconstituents. The study involved formulating a gel base incorporating Acalypha indica phytoniosomes and evaluating its physicochemical properties (pH, viscosity, spreadability) and in vitro release characteristics. The developed gel demonstrated promising anti-inflammatory potential, with sustained release of Acalypha indica phytoconstituents. This research provides a foundation for further investigation into the clinical application of this novel gel formulation for the management of inflammatory skin conditions.